The Hudson's Bay Company and Mr. Julian Ralph [electronic resource] - Martin, Archer, 1865-1941.; Ralph, Julian, 1853-1903. A skin for a skin. ([S.l. : s.n., 1892)
Review of Ralph's article in Harper's New Monthly Magazine entitled " A Skin for a skin". From: The Manitoban. Caption title. Electronic reproduction. Mode of access: Internet. 44